Estructura financiera de los gastos públicos en la Municipalidad Distrital de San Juan Bautista, periodo 2019 – 2023 - Silva Galvez, Julio Cesar (2025)
Knowledge of the financial structure regarding public spending in a state entity is important, since it allows senior management to have relevant information to make decisions regarding the execution of spending, seeking to ensure that they are efficient and comply with their objectives. purpose. The purpose of the research is to identify the financial structure of public spending in the district municipality of San Juan Bautista, its scope of study being a period of five (05) years. In addition, the population was made up of all data records. related only to public spending, various techniques were used as well as an instrument for collecting information; regarding the methodology used, it presents a quantitative approach, with a descriptive level, with a non experimental – longitudinal design. The results achieved allowed us to identify that public expenses are comprised of operational activities linked to their nature.